2010
DOI: 10.1038/oby.2009.191
|View full text |Cite
|
Sign up to set email alerts
|

BMI and Mortality: Results From a National Longitudinal Study of Canadian Adults

Abstract: Although a clear risk of mortality is associated with obesity, the risk of mortality associated with overweight is equivocal. The objective of this study is to estimate the relationship between BMI and all‐cause mortality in a nationally representative sample of Canadian adults. A sample of 11,326 respondents aged ≥25 in the 1994/1995 National Population Health Survey (Canada) was studied using Cox proportional hazards models. A significant increased risk of mortality over the 12 years of follow‐up was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
134
3
6

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(158 citation statements)
references
References 20 publications
15
134
3
6
Order By: Relevance
“…Consistent with previous findings in the literature [20,21,23,26,56], our findings showed that higher degrees of obesity and underweight were associated with higher mortality. But deviating from Berrington de Gonzalez et al [20] and others [19,21], our BMI-mortality association approximated a U-shaped relationship with the lowest mortality rate in the overweight classification [23,24,26,56], while theirs approximated a J-shaped relationship with the lowest mortality rate in the normal-weight classification.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Consistent with previous findings in the literature [20,21,23,26,56], our findings showed that higher degrees of obesity and underweight were associated with higher mortality. But deviating from Berrington de Gonzalez et al [20] and others [19,21], our BMI-mortality association approximated a U-shaped relationship with the lowest mortality rate in the overweight classification [23,24,26,56], while theirs approximated a J-shaped relationship with the lowest mortality rate in the normal-weight classification.…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with previous findings in the literature [20,21,23,26,56], our findings showed that higher degrees of obesity and underweight were associated with higher mortality. But deviating from Berrington de Gonzalez et al [20] and others [19,21], our BMI-mortality association approximated a U-shaped relationship with the lowest mortality rate in the overweight classification [23,24,26,56], while theirs approximated a J-shaped relationship with the lowest mortality rate in the normal-weight classification. This deviation can be explained by at least three reasons: (i) our study adjusted for ORDs, and hence, the nadir for death rates shifted slightly to the right in the range of overweight; (ii) only whites were included in the sample of Berrington de Gonzalez et al [20], eliminating ethnic variation, which is known to be a key determinant of obesity-mortality relationships; (iii) unobserved heterogeneity was not controlled for in their analyses; thus, the sample was selected toward survivors.…”
Section: Discussionsupporting
confidence: 83%
“…2 In white populations, ex tremely low and high BMI values were found to be associated with an excess risk of death in several nationwide studies. [3][4][5] In a more recent study involving 11 326 Canadians aged 25 years or older, Orpana and colleagues found that both underweight (BMI < 18.5) and severe obesity (BMI ≥ 35) were strong risk factors for all-cause mortality. 4 However, the optimal BMI values reported in the two Chinese studies 1,2 were higher than those reported in the white populations.…”
mentioning
confidence: 99%
“…[3][4][5] In a more recent study involving 11 326 Canadians aged 25 years or older, Orpana and colleagues found that both underweight (BMI < 18.5) and severe obesity (BMI ≥ 35) were strong risk factors for all-cause mortality. 4 However, the optimal BMI values reported in the two Chinese studies 1,2 were higher than those reported in the white populations. For example, on the basis of data from 19 prospective studies involving a total of 1.46 million white adults, Berrington de Gonzalez and colleagues found that BMI values of 22.5-24.9 were optimal in white adult populations.…”
mentioning
confidence: 99%
“…Obesity not only puts individuals at increased risk of death from numerous causes (Flegal, Graubard, Williamson, & Gail, 2007;Orpana et al, 2010), but it also poses economic hardships on individuals and business alike. As an example, obese individuals pay an average of 42% more for health care expenses than normal-weight individuals, and insurance agencies such as Medicare incur over $1,000 more in costs for obese than normalweight patients (Finkelstein, Trogdon, Cohen, & Dietz, 2009).…”
mentioning
confidence: 99%